Evaluation of potential risk of transmission of avian influenza A viruses at live bird markets in response to unusual crow die‐offs in Bangladesh. Issue 3 (7th January 2020) - Rahman, Mahbubur; Mangtani, Punam; Uyeki, Timothy M.; Cardwell, Jacqueline M.; Torremorell, Montserrat; Islam, Ariful; Samad, Mohammed A.; Muraduzzaman, A. K. M.; Giasuddin, Md; Sarkar, Sudipta; Alamgir, A. S. M.; Salimuzzaman, M.; et al.
Abstract: In response to unusual crow die‐offs from avian influenza A(H5N1) virus infection during January‐February 2017 in Dhaka, Bangladesh, a One Health team assessed potential infection risks in live bird markets (LBMs). Evidence of aerosolized avian influenza A viruses was detected in LBMs and in the respiratory tracts of market workers, indicating exposure and potential for infection. This study highlighted the importance of surveillance platforms with a coordinated One Health strategy to investigate and mitigate zoonotic risk.